P042 Does sleep inertia affect how we perceive time? – Implications for insomnia. (19th November 2019) - Crawford, Megan; Vallieres, Annie; Salanitro, Matt; Rees, Hannah; Carr, Michelle; Bradshaw, Ceri; Laroch, David; Nolin, Patricia; Delage, Julia; Blagrove, Mark
Abstract : Introduction: Sleep inertia (SI) can negatively affect cognitive functions including time perception. Accurate time perception is important for evaluating wakefulness at night. Overestimating wakefulness can be anxiety-provoking for individuals with insomnia. Here we present data from three studies testing the impact of SI on time perception after waking from sleep versus after a wake period. Methods: Participants were required to complete a time estimation task after waking from sleep and after a wakeful period. In study 1 and 2 (n=18), sleep occurred as part of a daytime nap with polysomnography. In study 3 (n=9) sleep occurred at night in a laboratory. Study 1 and 3 included good sleepers and study 2 included poor sleepers. The time estimation task was the same across all studies asking participants to state when they believed 15 minutes had passed, see figure 1 . Results: Data from study 1 and 2 were pooled. Participants overestimated time, however there was a greater overestimation after waking from a nap compared to the wake condition, t(17)=-2.089, p=0.052, d=0.7. For those individuals who reached stage 3 sleep during the nap (when waking with SI is more likely) the difference was significant, t (9)=-3.22, p<0.05, d=1.1). There was no main effect of sleep status (poor sleeper vs. good sleeper) on these differences. In study 3 there was no difference (p>0.05) between the two conditions (wake vs. sleep), see figure 2 for a summary of the findings. Conclusion: Overestimation of time awake was more pronounced after waking from a nap condition compared to after a wake period, especially when waking from stage 3 sleep. The same effects were not present when waking from sleep at night, perhaps due to different study designs. Further research in larger samples is needed to understand the impact of SI on time perception.